Differences in Mother's Knowledge, Energy Consumption, and Protein in Stunted Toddlers between Nutrition Education with Video Media and Without Video Media in Purwodadi Village, Blimbing District, Malang City - Farah Shabiyyah Kusumarini; I Nengah Tanu Komalyna; Tapriadi; I Dewa Nyoman Supariasa (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
ntroduction: Mothers' lack of understanding regarding MP-ASI will affect toddlers' nutritional intake. Nutrition education using video media can increase mothers' knowledge of the importance of meeting toddlers' nutritional intake. Objective: To analyze differences in maternal knowledge levels, levels of energy consumption, and protein in stunted toddlers between nutrition education with video media and without video media in Purwodadi Village, Kec. Blimbing, Malang City. Method: The research method used is a quasi-experimental method with a two-group pre and post-test design, a purposive sampling technique. The total sample obtained was 18 mothers of toddlers who were divided into two groups. Education was carried out three times, and each time the education was carried out for 60-90 minutes. The knowledge of mothers of toddlers, energy, and protein consumption of toddlers before and after were tested using the Paired Sample T-Test because the data was normally distributed, while the knowledge of mothers of toddlers, energy, and protein consumption of toddlers between the treatment and control groups used the Independent Sample T-Test. Result: The research results showed that the average knowledge before education was (62.2 ± 11.7) and after (92.8 ± 6.1) in the treatment group, while in the control group, the average knowledge of nutrition before education was (62.2 ± 11.7) and after (79.4 ± 6.8). The average energy consumption of toddlers in the treatment group before education was (66.3 ± 11.6) and after (98.5 ± 8.6), while in the control group, the average energy consumption of toddlers before education was (70.9 ± 26.3). and after (88.2 ± 26.3). Apart from that, the average protein consumption in the treatment group before education was (70.3 ± 13.1) and after (96.2 ± 11.0), while in the control group, the average protein consumption before education was (76.6 ± 23.5). and after (83.1 ± 21.9). Apart from that, there were differences in nutritional knowledge of mothers of toddlers, energy consumption, and protein for toddlers between education with video media and without video media (p<0.05). These results are presented in Tables 8, 10, and 12 to see any differences between the treatment and control groups. Conclusion: This research concludes that there are differences in maternal knowledge, energy consumption, and toddler protein between nutrition education with video media and without video media.